Long-term pair bonds and male parental care in Speckled Teal Anas flavirostris in Eastern Argentina - Port, Jeffrey L (Wildfowl, 1998)
The breeding behaviour of Specked Teal; hereafter teal, in eastern Argentina, is influenced strongly by their preference for Monk Parakeet nest cavities. I observed a marked population (n=337) on the Estancia Los Yngleses, province of Buenos Aires, Argentina from August to December between 1991 and 1994. All pair bonds between marked pairs (n=38) were monogamous and typically lasted at least two breeding seasons and some lasted at least six years (mean = 2.24 1.12, range 1-6). The probability of divorce was 10.6% and five divorces were recorded in a total of 28 pairs observed over four breeding seasons. Most mate changes (71.5%) followed the disappearance of one pair member. Competition among males for mates was intense. Eight of nine males failed to re-pair following mate loss and many males unpaired at the beginning of the study (16 of 21) were thought to remain unpaired during the study. Only females (n = 7) were successful in re-pairing following the loss of a mate. Males were present with the female and brood in all families observed (n = 9) and the absence of male sightings following exodus from the nest area (n = 33) provided circumstantial evidence that males remained with the female and brood throughout the brood-rearing period. Males escorted broods, retrieved ducklings that strayed, shared alert time with females, and performed distraction displays.